The Encyclopedia of Applied Linguistics 2012
DOI: 10.1002/9781405198431.wbeal0694
|View full text |Cite
|
Sign up to set email alerts
|

Lexical Priming

Abstract: Lexical priming is the name given to a linguistic theory developed by Michael Hoey (in particular in Hoey, 2003, 2004a, 2005), which seeks to relate corpus‐linguistic concepts such as collocation and colligation to the experimental findings of psycholinguists interested in the retardation and acceleration of word association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 17 publications
2
8
0
1
Order By: Relevance
“…Previous studies found that word forms and lemmas display different collocational patterns in corpora (Hoey, 2005;Tognini-Bonelli, 2001). Although investigating collocational patterns of individual word forms is interesting for linguistic purposes, as the aims of the present study were primarily pedagogical, examining lemmas was found to be more appropriate as this provides an adequate level of detail to language learners (Nation, 2016).…”
Section: Collocation Analysismentioning
confidence: 80%
“…Previous studies found that word forms and lemmas display different collocational patterns in corpora (Hoey, 2005;Tognini-Bonelli, 2001). Although investigating collocational patterns of individual word forms is interesting for linguistic purposes, as the aims of the present study were primarily pedagogical, examining lemmas was found to be more appropriate as this provides an adequate level of detail to language learners (Nation, 2016).…”
Section: Collocation Analysismentioning
confidence: 80%
“…As a further explanation for why knowledge of NLS does not fully develop in the majority of late learners, we can consider Hoey's (2005) work on lexical priming. He argues that when a word is learned in a L2, initially at least, it will activate the related collocational and syntagmatic relationships of its L1 counterpart, and these are not likely to be nativelike to the L2.…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing on learners' written production of NLSs (most often operationalized as collocations) have found that learners systematically deviate from native norms through over-or underuse (e.g., Granger, 1998 ;Nesselhauf, 2005 ) and are particularly susceptible to cross-linguistic infl uence (e.g., Laufer & Waldman, 2011 ). Hoey ( 2005 ) notes that L2 learners in a classroom are not in an environment rich enough for them to be able to build nativelike networks of L2 word associations, and, so, what he terms L1 primings are likely to be activated, unhelpfully, by L2 words.…”
Section: Vocabulary Selection In a Second Languagementioning
confidence: 99%
See 1 more Smart Citation
“…Экстенсивное чтение является залогом обучения языку и положительно влияет на уровень понимания прочитанного, владения лексикой, орфографических навыков, общих культурных знаний [8; 14-15; 18]. В овладении иностранным языком существенно важно количество вводимой информации (input), и расширенное чтение больших объемов текста признаётся одним из эффективных способов изучения новой лексики и закрепления пройденной [7]; здесь также имеет место так называемый лексический прайминг [10], в процессе которого обучающийся сталкивается с лексическими единицами в различных контекстах и получает о них дополнительные сведениязначения и коннотации, коллокации и коллигации, стиль и регистр и др. Более того, экстенсивное чтение имеет шанс трансформироваться в так называемое чтение для удовольствия (reading for pleasure), вызывающее положительные эмоции и выступающее в роли позитивного подкрепления изучения иностранного языка [9].…”
Section: послетекстовый этапunclassified